An observational study to assess male gender as an isolated risk factor in the laparoscopic cholecystectomy - Songra, Bhupen; Kumar, Amit; Jain, Mohit; Jalendra, Gaurav (International Surgery Journal, 2021)
Background: Laparoscopic cholecystectomy is the procedure of choice for majority of patients with gall bladder disease. The aim of the study was to investigate the role of male gender as an isolated risk factor responsible for the increased peri-operative morbidity of laparoscopic cholecystectomy by excluding associated risk factors. Methods: This was a prospective observational descriptive study 60 cases of elective laparoscopic cholecystectomy admitted to the S. M. S. Hospital from July 2019 to May 2020 were included. Results: The most common age group in male was 41-50 years and in female was 51-60 years. Impacted stones and gall bladder wall thickness >4 mm was causes of difficult cholecystectomy and evenly distributed in both sexes. Operative time (p value=0.268), visual analogue score on day 1 (p value=0.307) and hospital stay (p value=0.376) was more in male group but not statistically significant. Conclusions: Impacted stone and gall bladder wall thickness >4 mm were only factors associated with difficult laparoscopic cholecystectomy and excludes male gender as an isolated risk factor for difficult cholecystectomy however large-scale studies may provide different results.